2008
DOI: 10.3758/mc.36.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during the reading of compound words and the influence of lexeme meaning

Abstract: Compound words are formed by combining free lexemes into a single lexicalized expression. Few rules govern this lexical-conceptual "evolution." In English, lexicographers find new compounds by examining popular usage-that is, words used together relatively often to denote a specific concept. Most compounds become "solid"-that is, are written as spatially unified expressions-but others are written with a blank space between the lexeme constituents or are hyphenated. One central question in the study of compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 33 publications
(59 reference statements)
5
39
0
Order By: Relevance
“…If the frequency of a compound's constituent lexemes influences processing times on the compound, then it follows that those lexemes are accessed during the recognition of the full compound. The results of most studies with English compound words converge in showing a functional role for lexemes during compound processing using a variety of tasks such as word naming, lexical decision, and eye movements during sentence reading (e.g., Andrews, 1986;Andrews, Miller, & Rayner, 2004;Inhoff, Starr, Solomon, & Placke, 2008;Juhasz, 2007Juhasz, , 2008Juhasz, , 2012Juhasz, Starr, Inhoff, & Placke, 2003). These results with English compounds share many similarities to those observed in languages such as Finnish (e.g., Hyönä & Pollatsek, 1998;Pollatsek, Hyönä, & Bertram, 2000) in which compounding is more productive.…”
Section: Lexical Decomposition Of Compound Wordssupporting
confidence: 63%
See 2 more Smart Citations
“…If the frequency of a compound's constituent lexemes influences processing times on the compound, then it follows that those lexemes are accessed during the recognition of the full compound. The results of most studies with English compound words converge in showing a functional role for lexemes during compound processing using a variety of tasks such as word naming, lexical decision, and eye movements during sentence reading (e.g., Andrews, 1986;Andrews, Miller, & Rayner, 2004;Inhoff, Starr, Solomon, & Placke, 2008;Juhasz, 2007Juhasz, , 2008Juhasz, , 2012Juhasz, Starr, Inhoff, & Placke, 2003). These results with English compounds share many similarities to those observed in languages such as Finnish (e.g., Hyönä & Pollatsek, 1998;Pollatsek, Hyönä, & Bertram, 2000) in which compounding is more productive.…”
Section: Lexical Decomposition Of Compound Wordssupporting
confidence: 63%
“…The results of both Marelli and Luzzatti (2012) and Inhoff et al (2008) suggest that semantic information can affect early morphological processing. The finding that activation of a compound word's semantic representation can influence its initial processing brings up the question of what exactly is contained in the semantic representation of a compound word.…”
Section: Lexeme Meaning Dominancementioning
confidence: 89%
See 1 more Smart Citation
“…Subjective frequency and familiarity ratings may therefore be tapping (2000) detected a significant frequency advantage (i.e., shorter fixation duration) for the first lexeme only on the first fixation; frequency effects for the compound words and all constituent lexemes were observed when total gaze duration (i.e., the sum of all fixation durations on a word prior to moving to another word) was examined (for similar results, see Andrews, Miller, & Rayner, 2004). Follow-up studies have found that the magnitude of the constituent frequency effect was larger for the lexeme that contributes most to the meaning of the whole compound word (i.e., dominant vs. nondominant constituent; Inhoff et al, 2008). It may indeed be more efficient to process constituent lexemes, which are often more familiar than the full form, as the meaning of the compound word is accessed.…”
Section: Word Frequency As a Determinant Of Lexical Processingmentioning
confidence: 76%
“…Using the same methodology, other studies have reported a significant constituent frequency effect for the first lexeme only (Taft & Forster, 1976), for the second lexeme only (Duñabeitia, Perea, & Carreiras, 2007;Juhasz, Starr, Inhoff, & Placke, 2003), or for both lexemes (Andrews, 1986;Inhoff, Starr, Solomon, & Placke, 2008;Zwitserlood, 1994). 1 These studies suggest that the pattern of frequency effects in compound word processing could depend on the way compound words are constructed in different languages, task requirements, the dependent variables being measured, and/or the interactions among these factors.…”
Section: Methods Participantsmentioning
confidence: 94%